2020
DOI: 10.1159/000508210
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of miR-340-5p against Brain Injury after Intracerebral Hemorrhage by Targeting PDCD4

Abstract: <b><i>Objective:</i></b> Intracerebral hemorrhage (ICH) is a common cerebrovascular disease. Increasing evidence has documented the crucial role of microRNAs in ICH. The present study aimed to investigate the role and underlying mechanism of miR-340-5p in ICH. <b><i>Methods:</i></b> The collagenase-induced ICH rat model was established. The neurological function of rats and the cerebral water content of rat brain tissue were measured to assess the brain injury. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It has been reported that miR‐340‐5p mitigates oxygen‐glucose deprivation/reoxygenation‐induced neuronal injury through targeting neuronal differentiation 4 (Zheng et al., 2020 ). Additionally, miR‐340‐5p targets PDCD4 to reduce inflammatory response and ameliorate intracerebral hemorrhage‐induced brain injury (Zhou et al., 2020 ). Also, miR‐340‐5p mitigates spinal cord injury‐induced neuroinflammation and neuronal apoptosis via modulating the p38‐MAPK signaling pathway (Qian et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that miR‐340‐5p mitigates oxygen‐glucose deprivation/reoxygenation‐induced neuronal injury through targeting neuronal differentiation 4 (Zheng et al., 2020 ). Additionally, miR‐340‐5p targets PDCD4 to reduce inflammatory response and ameliorate intracerebral hemorrhage‐induced brain injury (Zhou et al., 2020 ). Also, miR‐340‐5p mitigates spinal cord injury‐induced neuroinflammation and neuronal apoptosis via modulating the p38‐MAPK signaling pathway (Qian et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, many miRNAs, such as miR‐124 and miR‐193b‐3p, are also found to be dysregulated during the pathogenesis of SAH (Chen et al., 2020 ; Lai et al., 2020 ). Reportedly, miR‐340‐5p can reduce cerebral hemorrhage and spinal cord injury‐induced nerve injury and play a protective role by inhibiting neuroinflammation (Qian et al., 2020 ; Zhou et al., 2020 ), but its expression and function in SAH have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…To explore the mechanism of baicalein on brain injury after ICH, we established a model of brain injury after ICH by collagenase induction, and then ICH model was treated by baicalein. Neural function and brain tissue water content are widely used to evaluate the degree of brain injury after ICH [25]. The results showed that after baicalein treatment, nervous system damage, lesion volume and brain water content were decreased, cell apoptosis was decreased, the number of Nissl bodies was increased, and pathological severity signi cantly was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA played an important role in a series of key biological processes, including cell proliferation, differentiation and metabolism [21]. Numbers of miRNAs have been revealed play crucial roles in intracerebral hemorrhage, such as miR-124, miR-340-5p and miR-26a-5p [22][23][24]. However, there was less studies focus on HICH regulated by miRNAs.…”
Section: Discussionmentioning
confidence: 99%